Síntese de 1,2,3-triazóis com potencial atividade biológica e como precursores de carbenos mesoiônicos n-heterocíclicos - Luiza Baptista de Oliveira Freitas (2014)
This thesis is divided into two chapters. Chapter I refers to the synthesis and biological evaluation of 1,4-disubstituted 1,2,3-triazoles containing a quinoline or nicotine moiety. Chapter II refers to the synthesis of complexes of mesoionic carbenes with boranes, generated from 1,2,3-triazole nucleus, and their applications in reduction ofcarbonyl compounds and hydroboration of alkene. The first chapter describes the synthesis of 28 novel molecules derived from1,2,3-triazoles obtained in satisfactory yields by "click" reaction (CuI-catalyzed Huigsen cycloaddition) between azides and alkynes. The 1,2,3-triazole rings were linked to a quinolinic or nicotinic nucleus and to a glycoside or an aromatic group. Most of the synthesized products were subjected to biological assays in order to evaluate their antiproliferative, antibacterial and antifungal activities. The second chapter describes the synthesis of mesoionic carbenes (MICs) and their complexes with boranes, using salts of 1,4-disubstituted 1,2,3-triazoles asprecursors. Different routes to obtain stable complexes MIC-borane are described and some attempts to obtain chiral complexes are discussed. The applications of these MICs borane complexes were evaluated in reductions of the carbonyl group of aldehydes and ketones, and in hydroboration reaction. The MICs-BH3 adducts shown to be effectivereducing agents, being able to transfer all hydride equivalents for the reduction of carbonyls. The in situ generation of borenium ions from MIC-boranes using trityl salts was the strategy used to promote the hydroboration of allylbenzene.